Effectiveness of intervention by accredited social health activists in the control of hypertension and diabetes in a rural population of Kolar district, Karnataka - Surekha, A.; Fathima, Farah N.; Agrawal, Twinkle; Suguna, A.; Misquith, Dominic (International Journal Of Community Medicine And Public Health, 2019)
Background: Non-communicable diseases are the leading causes of death globally, of which cardiovascular diseases are the most common. Cost-effective strategies, such as task shifting, are needed to mitigate the rising epidemic by controlling hypertension and diabetes in our country. Methods: This was a non-randomized interventional study undertaken in six (3 intervention and 3 control) villages of Lakkur primary health centre (PHC) area under Malur taluk, Kolar district, Karnataka, from November 2013 to April 2015. After obtaining written informed consent, baseline survey was done among 180 diabetics and hypertensives (adults>30 years). In the intervention villages, ASHAs who were trained did the intervention for 6 months. In non-intervention villages, standard usual care was given and repeat survey was done after 6 months to re-measure. Results: This study demonstrated that there was an increase of 44.8% in the proportion of hypertensives whose blood pressure was under control and increase of 26.5% in the proportion of diabetics whose blood sugar was under control in villages that received household visits by trained ASHAs (intervention villages). There was an increase in the medication adherence levels (29.6%) and reduction in tobacco usage (median difference of 4 times per day) among hypertensives and diabetics who are on medication in intervention villages. Conclusions: Findings from this study will provide policy makers and other stakeholders needed information to recommend scalable and cost-effective policy in respect to cardiovascular risk reduction, hypertension and diabetes control in resource-poor settings.